(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Since last 2-3 decades, multi-level marketing firms entered in India to practice business activities by providing consumer – related goods like food grains, cosmetics, durables etc. this new trending industry competing with the traditional giants like HUL, Godrej and many more who were serving goods and services from pre-independence to post independence period. Now a days, consumers are more educated and distinguish the products and services in terms of price, durability, usages, benefits, quality and many more factors. Competitive advantage help the firm to bring quality work in their business and try to provide the best products to the customers in good quality, maximum usage & benefits and reasonable price which is the primary necessity of Indian customers. Customization of goods and making availability of products and services in a convenient manner is the biggest challenge for any business faced in today’s scenario for that reason they try to encounter and make contract deals with many stores, outlet, e-commerce businesses, distributors to market and make available their goods and services to the consumers for the purpose of consumption, satisfaction and generation of revenue for the business and their stakeholders. Customization and convenience factors are more to be focused for the acquisition of large market share can benefit the party i.e., consumers and commercial firm.